CONFLICTUAL SITUATIONS IN THE EDUCATIONAL UNITS - REALITY AND GOOD MODELS - Luminita Catana (National Centre for Policy and Evaluation in Education, 2013)
The conflict situations are everyday realities in any organization, therefore their analysis and management involved many specialists, due to the impact on individual and organizational performances. The concrete way of dependence between the tasks that employees have to solve and conflicts that arise are still unclear. This article collects qualitative information, as well as quantitative information from some recent projects deployed in our country or foreign countries, so that it clarifies to some extent the sources, types of conflicts and their frequency of occurrence. Also in the article there are presented some methods of analysing conflictual situations.